PEMBELAJARAN SASTRA BERBASIS KOMPETENSI DI SEKOLAH MENENGAH *) - Hartono, Hartono (Jurnal Cakrawala Pendidikan, 2005)
AbstractIn order to make-up of education quality in Indonesia, government have several times to conduct the changing of school curriculum. But that way, study at school still not yet maximal, include of literature learning which until now still have many insuffiency. Curriculum Base on Competention application in the year teaching 2004 expected can bring the repair in a learning program include literature study.Until now literature learning at senior/junior high school still have a lot of criticed because didnt maximal to realizing education target, specially education of kindness of ethic or student personality. For that, literature learning have to actualized and be optimalized. The reactualizationand optimalization for example can be through by improving role and creativity the teacher of literature learning in learning process and change the orientation learning to ward the learning process to studentorientation and also provide the reading book complete literature in school library.Key words: literature learning, learning based competence, children oriented